Lotfi Mansouri an operatic journey - Mansouri, Lotfi; Arthur, Donald (Northeastern University Press ; Published by University Press of New England, 2010)
A lively and engaging memoir of one of opera's driving forces
Keywords: Mansouri, Lotfi; Opera producers and directors : Biography